Revisiting the relationship between justice and extra-role behavior: the role of state ownership - Chen, Xi (Cambridge University Press, 2018)
State ownership is an important phenomenon in the world economy, especially in transition economies. Previous research has focused on how state ownership influences organizational performance, but few studies have been conducted on how state ownership influences employees. I propose that different ownership structures trigger different relational models among employees who pay attention to organizational justice consistent with their model to guide their extra-role behavior. Specifically, state-owned organizations reinforce employees’ relational concern and direct employees’ attention to procedural justice, whereas privatized organizations highlight employees' instrumental concern and direct their attention to distributive justice. I leverage a sample of organizations in China to explore how different ownership structures activate different relational models among employees and alter the relationship between organizational justice and employees’ extra-role behaviors. I find that state ownership attenuates and even reverses the positive relationship between distributive justice and extra-role behaviors. Conversely, state ownership exaggerates the positive relationship between a critical procedural justice dimension (participation in decision making) and employee extra-role behaviors. Implications for the micro-foundations of corporate governance and institutional change, organizational justice literature, and cross-cultural research are developed. This study also generates new insights for transition economies such as China.